Coire Sois, The Cauldron of Knowledge : a Companion to Early Irish Saga - Uí Cathasaigh, Tomás (University of Notre Dame Press, 2014)
"Coire Sois, The Cauldron of Knowledge: A Companion to Early Irish Saga offers thirty-one previously published essays by Tomas Ó Cathasaigh, which together constitute a magisterial survey of early Irish narrative literature in the vernacular. Ó Cathasaigh has been called "the father of early Irish literary criticism," with writings among the most influential in the field. He pioneered the analysis of the classic early Irish tales as literary texts, a breakthrough at a time when they were valued mainly as repositories of grammatical forms, historical data, and mythological debris. All four of the Mythological, Ulster, King, and Finn Cycles are represented here in readings of richness, complexity, and sophistication, supported by absolute philological rigor and yet easy for the non-specialist to follow. The book covers key terms, important characters, recurring themes, rhetorical strategies, and the narrative logic of this literature. It also surveys the work of the many others whose explorations were launched by Ó Cathasaigh's first encounters with the literature. As the most authoritative single volume on the essential texts and themes of early Irish saga, this collection will be an indispensable resource for established scholars, and an ideal introduction for newcomers to one of the richest and most under-studied literatures of medieval Europe. "Tomas Ó Cathasaigh is that rare scholar in Celtic studies whose work has much to say not only to advanced scholars in the field but also to specialists dealing with other literatures, comparative mythologists, and undergraduates. Our understanding of medieval Irish epic and saga is immeasurably enriched by his elegant writing style, his erudition, and his wide-ranging critical eye. It is indeed a bounteous blessing, then, to have collected in this volume Ó Cathasaigh's best, most representative, and most useful work." --Joseph Nagy, University of California, Los Angeles"